Interpretation Of Ummatan Wahidatan According To H.O.S Tjokroaminoto's Thoughts On The Life Pattern Of The Sharia Economic Community In Indonesia - Prasetio, Andri (Zona Law And Public Administration Indonesia, 2024)
The world community knows the capitalist economic system, the socialist economic system and the Islamic economic system. However, very little research has been done on the socialist economic system. More or less 100 years ago, HOS. Cokroaminoto has discussed socialism and its similarities with Islam. The presence of this research has the following objectives: 1). Examining how HOS. Cokroaminoto reconstructed socialism with Islamic religious principles. 2). Reconstructing a socialist economic system based on Islamic religious principles prepared by HOS. Cokroaminoto. The research that the author conducted is library research, especially a study of the thoughts of characters. The approach and research method used is dialogical hermeneutics. The data required for this research was obtained from primary and secondary sources related to HOS. Cokroaminoto. These data were then analyzed using taxonomic analysis methods. The results of the analysis are arranged according to categories to answer the problem formulation or research objectives of this thesis. The results of this research produce two conclusions. First, HOS. Cokroaminoto interprets socialism as almost the same principle as friendship. In a friendship relationship, each party involved has an equal position. Regardless of their respective positions or social status. Second, HOS's interpretation of Islamic socialism. Cokroaminoto in the economic scope is divided into at least four sub-sections. 1). Land Rights (Agrarian) Affairs, 2). Transactional Concept, 3). Morals and Trade Practices, 4). People's Priorities. In contrast to the secular socialist economic system which does not recognize private ownership, the Islamic method of socialism is HOS. Cokroaminoto still recognizes private ownership. Reaping profits in a trade transaction is also still permitted as long as it is not done in ungodly ways. In general, the concept of socialism in the Islamic way of HOS. Cokroaminoto must first prioritize the interests of the people over personal interests